(untitled) (International Journal of Physiotherapy, 2021)
Background: In modern days, football players require specific stamina and body composition to perform well in various playing positions such as goalkeeper, defenders, midfielders, and forwards. This study was aimed to examine the body composition and endurance capacity of Pakistani national football players. Data was collected from national football players by considering their playing position. Methods: The selected variables were height, weight, eight skinfolds, the sum of skinfolds, cover distance in a match, and yo-yo intermittent test. One-way analysis of variance (ANOVA) was applied for statistical analysis. Results: Results showed that the goalkeepers were significantly superior in height and weight than the midfielders and defenders. On the other hand, goalkeepers were significantly inferior in endurance capacity and covered distance than the midfielders and defenders. Conclusion: The midfielders and defenders cover a longer distance during a match which depicts their higher endurance capacity than the goalkeeper and forward. These findings would be useful to address the advancement in football performance and team selection. Therefore, coaches should focus on a training session by considering the playing positions of players.